Effect of Bee Population & Bee Venom Milking during Spring and Early Summer in s some of Honey Bees (Apis Mellifera L.) Colonies Biological Characters (NTU Journal of Agriculture and Veterinary Science, 2023)
The results of the current study conducted in the apiary of the College of Agriculture and Forestry / University of Mosul during the year 2021 showed that the highest amount mean of bee venom for the interaction reading was 0.232 mg/colony in the treatment of milking bee population 10 frames (TMV2) during the period from 1-6/5/2021 compared with the lowest mean interaction of 0.061 which was recorded during the period from 6/26-1/7 for the same treatment, while the highest mean interaction for the treatment of milking bee venom population of 5 frames (TMV1) during the period from 1-6/5 /2021 was 0.125 mg/colony compared with the lowest mean of 0.022 mg/colony during the period from 29/5 to 3/6/2021 for the same treatment. As for the treatment general mean, the highest mean was recorded by the TMV2 treatment which mounted to 0.1136 mg/colony compared with the lowest general mean of zero mg/colony by the TCM2 treatment. As for the milking treatment of TMV1, the highest mean recorded was 0.0527 mg/colony by the TMV1 treatment compared with the lowest average of zero mg/colony by the TCM1 treatment. As for the process effect of the bee venom milking on bee population, the bee popu lation decreased by 1.12 bee frame by the TMV2 treatment which recorded a mean of 14.15 bee frames compared with the TCM2 treatment that, in turn, recorded a mean of 15.27 bee frames. As for the treatments with a bee population of five frames, the bee population decreased by 1.30 bee frames by the treatment of TMV1 which recorded the lowest mean of 8.07 bee frames compared with the highest mean of 9.37 recorded by the TCM1 treatment. As for the general mean of the sealed workers brood, the statistical analysis did not show any significant differences between the two treatments; namely, the TMV2 and the TCM2 whose means both reached to 394.89 inch2 and 367.37 inch2 respectively. Regarding the treatments with bee population of five frames, the highest mean was recorded by the treatment TCM1 amounting to 315.98 inch 2 compared with the lowest mean of 245.07 recorded by the TMV1 treatment. As for the pollen area in treatments with a bee population of 10 frames, the highest mean was recorded by the TCM2 treatment which mounted to 66.78 inch2 compared with the lowest mean in the TMV2 treatment which mounted to 61.44, and the statistical analysis did not show significant differences for the effect of milking bee venom. In the pollen mean for the treatments with a bee population of five frames, the highest mean was recorded by the TCM1 treatment which reached to 65.11 inch2 compared with the lowest mean of 54.63 inch2, recorded by the TMV1 treatment.